RealWorld evaluation working under budget, time, data, and political constraints - Bamberger, Michael (Thousand Oaks SAGE, 2012)
This book addresses the challenges of conducting program evaluations in real-world contexts where evaluators and the agencies face budget and time constraints and where critical data is missing. The book is organized around a seven-step model developed by the authors, which has been tested and refined in workshops. Vignettes and case studies―representing evaluations from a variety of geographic regions and sectors―demonstrate adaptive possibilities for small projects with budgets of a few thousand dollars to large-scale, long-term evaluations. The text incorporates quantitative, qualitative, and mixed-method designs
Includes bibliographical references and indexes.
Keywords: Evaluation research (Social action programs)--Developing countries